Role Of Women In Manju Kapur’s ‘Home’ - Dr. N.Sujata; Dr. K.Ahalya Sundari (Educational Administration: Theory and Practice, 2023)
Manju Kapur’s women are the personification of ‘New Woman’ representing the new voice of new social order. Casting aside the burden of inhibition since ages they now want to breathe the air freedom and assert a position of respectability. The present paper discusses how Kapur’s Home successfully presents the real picture of a woman in a male-dominated society. Here the protagonists are tossed in the struggle between tradition and modernity, conservationism and newness, and call of conscience and the demand of tradition. The tension between these notions of identity and the desire for personal fulfilment forms the thematic foundation of the novel.